2015
DOI: 10.1016/j.jsps.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of 5-Fluorouracil enteric coated nanoparticles for sustained and localized release in treating colorectal cancer

Abstract: 5-Fluorouracil is used in the treatment of colorectal cancer along with oxaliplatin as first line treatment, but it is having lack of site specificity and poor therapeutic effect. Also toxic effects to healthy cells and unavailability of major proportion of drug at the colon region remain as limitations. Toxic effects prevention and drug localization at colon area was achieved by preparing enteric-coated chitosan polymeric nanoparticles as it can be delivered directly to large bowel. Enteric coating helps in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 17 publications
4
55
0
2
Order By: Relevance
“…In vitro drug release for 5-FUEC in various simulated fluids representing GIT pH had conformed its stability in acidic pH and there after releasing the drug in the basic pH. Drug release was found to be only after 4 h once it enters the intestinal fluid and was localized along with its sustained release over a period of 24 h (Tummala et al, 2015b). In this study, extensive cellular and apoptotic studies were carried out to investigate the apoptotic activity of the 5-FUEC using Annexin-PI assay (using flow cytometry) and Acridineorange/Ethidium bromide method.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In vitro drug release for 5-FUEC in various simulated fluids representing GIT pH had conformed its stability in acidic pH and there after releasing the drug in the basic pH. Drug release was found to be only after 4 h once it enters the intestinal fluid and was localized along with its sustained release over a period of 24 h (Tummala et al, 2015b). In this study, extensive cellular and apoptotic studies were carried out to investigate the apoptotic activity of the 5-FUEC using Annexin-PI assay (using flow cytometry) and Acridineorange/Ethidium bromide method.…”
Section: Resultsmentioning
confidence: 90%
“…We emphasized mainly on the localization of the drug in the target area, thereby minimizing the chances of drug distribution to the other organs in our previous studies (Tummala et al, 2015b). Essentially, coating of anti-neoplastics with polymers comprising of the classes like cellulose derivatives (Levine et al, 1987), acrylic polymers (Rasmussen et al, 1982) etc., that can deliver major amount of the drug directly to the large bowel thereby bypassing the systemic circulation can be explored.…”
Section: Introductionmentioning
confidence: 99%
“…49 In another study, researchers prepared chitosan polymeric NPs by the solvent evaporation emulsification method, with varied ratios of polymer. 50 They concluded that the NPs prepared by solvent evaporation emulsification using the polymer at the optimum ratio represents an approach for potentially successful delivery of the active pharmaceutical element to the colorectal tumors. 50 Total health centre complex N-38 is a highly effective drug against many cancers, as it contains pharmaceutically active ingredients.…”
Section: Applications Of Plga Nanoparticles/nanocellsmentioning
confidence: 99%
“…50 They concluded that the NPs prepared by solvent evaporation emulsification using the polymer at the optimum ratio represents an approach for potentially successful delivery of the active pharmaceutical element to the colorectal tumors. 50 Total health centre complex N-38 is a highly effective drug against many cancers, as it contains pharmaceutically active ingredients. However, the development of an optimal delivery system for SN-38 is challenging, owing to its low solubility and the presence of a labile lactone ring.…”
Section: Applications Of Plga Nanoparticles/nanocellsmentioning
confidence: 99%
“…Enteric coated dosage forms for the drug, like matrix tablets, microspheres or nanoparticles using polymers like Eudragit S100 or ethylcellulose have been used for such purposes. [6][7][8][9] Besides, novel drug delivery systems like modified pulsincap delivery, polyelectrolyte complexes, osmotic devices, etc were also tried out. [10][11][12] The answer to the second question may be determined by analysing available literature of drug dosing and pharmacokinetic data.…”
Section: Introductionmentioning
confidence: 99%